Analisis Pengaruh Indikator Brand Resonance Terhadap Brand Loyalty Pada Konsumen Restoran Berlabel Halal di Solo Raya - Delfiya Anggraini; Moechammad Nasir (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study aims to examine (1) the effect of brand credibility, (2) the effect of service quality, (3) the effect of customer satisfaction, and (4) the effect of brand association on brand loyalty among users of halal-certified restaurants in Solo Raya. This research employs a quantitative approach. The population of this study includes individuals who visit halal-certified restaurants in the Solo Raya area. Sampling was conducted using a non-probability sampling method, with a total sample size of 200 respondents. The study uses primary data collected through the distribution of questionnaires. The data analysis methods employed in this research include validity tests, reliability tests, multiple linear regression analysis, F-tests, t-tests, and the coefficient of determination (R²). The results of the study indicate that the variables brand credibility, service quality, customer satisfaction, and brand association collectively explain brand loyalty by 21.6%, while the remaining 78.4% is explained by other variables not examined in this study. Based on the findings, it was concluded that (1) brand credibility has a positive and significant influence on brand loyalty, (2) service quality has a positive and significant influence on brand loyalty, (3) customer satisfaction has a positive and significant influence on brand loyalty, and (4) brand association has a positive and significant influence on brand loyalty.